A novel nanofiltration membrane with simultaneously enhanced antifouling and antibacterial properties. Issue 11 (19th February 2019) - Qi, Yawei; Zhu, Lifang; Gao, Congjie; Shen, Jiangnan
Abstract : A novel nanofiltration membrane is prepared by using polydopamine (PDA) and hydroxyl propyl trimethyl ammonium chloride chitosan (HACC) mixed with chitosan (CN) and chelated silver (Ag) nanoparticles. Abstract : A novel nanofiltration membrane prepared by modification of a commercial membrane surface is fabricated using polydopamine (PDA) and hydroxyl propyl trimethyl ammonium chloride chitosan (HACC) mixed with chitosan (CN) and chelated silver (Ag) nanoparticles. The surface chemical composition, cross-sectional morphology, hydrophilicity and surface structure of the prepared membranes were examined by scanning electron microscopy, water contact angle measurements, and atomic force microscopy, respectively. The membrane performance was evaluated in terms of volumetric flux and protein rejection. In addition, the antifouling and antibacterial properties of the membranes were also explored. The results demonstrated that the prepared membranes exhibited an excellent antifouling property due to their three-layer architecture and it provided a special layer to promote the antibacterial property. According to the results, the modified membrane has a significantly improved flux recovery rate (over 96%). Besides, the antibacterial activity tests showed that the proposed three-layer architecture modification extensively prevented bacterial growth on the membrane surface.